Microplastic Abundance and Characteristics in Digestive Tract of Fish Tongkol Euthynnus affinis from Coastal Area of Ampenan, Mataram - Zoelvianti, Oktry; Zulkifli, Lalu; Syukur, Abdul; Karnan, Karnan (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2026)
The rise in plastic usage in Indonesia has resulted in a buildup of plastic waste both on land and in water bodies. Because it does not break down easily due to the lack of microorganisms that can degrade it, plastic remains in the environment and pollutes various living beings. Thus, it is important to conduct studies on microplastic contamination to evaluate the safety of fish, which is a widely eaten source of food. This study aimed to determine the abundance and characteristics of microplastics in Ikan Tongkol (Euthynnus affinis) from the coastal waters of Ampenan Beach. Sampling was conducted using a random sampling method. Tuna samples were collected from fishermen along the Ampenan coast three times, totaling 30 fish. The analysis was conducted through sample preparation, oxidation of organic matter, filtration, and microscopic observation. The results showed that microplastics had accumulated in the digestive tract of the Euthynnus affinis, with an abundance of 2.3 MP/Ind. The most dominant type of microplastic found was fiber, accounting for 65% of the total sample, with black being the predominant color. Four types of microplastics were identified in the digestive tract: 65% fiber, 20% fragments, 10% film, and 5% granules.